Area Deprivation Index as a Surrogate of Resilience in Aging and Dementia - Vassilaki, Maria; Petersen, Ronald C.; Vemuri, Prashanthi (Frontiers in Psychology, 2022)
Area deprivation index (ADI), a recently introduced tool to capture the multidimensional neighborhood socioeconomic disadvantage across populations, is highly relevant to the field of aging and Alzheimer's disease and Alzheimer's disease related dementias (AD/ADRD). ADI is specifically relevant in the context of resilience, a broad term used to explain why some older adults have better cognitive outcomes than others. The goal of this mini-review is three-fold: 1) to summarize the current literature on ADI and its link to cognitive impairment outcomes; 2) suggest possible mechanisms through which ADI may have an impact on AD/ADRD outcomes, and 3) discuss important considerations when studying relations between ADI and cognitive as well as brain health. Though difficult to separate both the upstream factors that emerge from high (worse) ADI and all the mechanisms at play, ADI is an attractive proxy of resilience that captures multifactorial contributors to the risk of dementia. In addition, a life-course approach to studying ADI may allow us to capture resilience, which is a process developed over the lifespan. It might be easier to build, preserve or improve resilience in an environment that facilitates instead of hindering physical, social, and cognitively beneficial activities. Neighborhood disadvantage can adversely impact cognitive impairment risk but be at the same time a modifiable risk factor, amenable to policy changes that can affect communities.